A MetAP2 inhibitor blocks adipogenesis, yet improves glucose uptake in cells. (2nd January 2019) - Siddik, Md Abu Bakkar; Das, Bhaskar C.; Weiss, Louis; Dhurandhar, Nikhil V.; Hegde, Vijay
ABSTRACT: Adipose tissue expansion involves angiogenesis to remodel its capillary network. The enzymemethionine aminopeptidase 2(MetAP2) promotes angiogenesis.MetAP2 inhibitors suppress angiogenesis and have potential anti-obesity effect. However, impairment in adipose tissue expansion is also linked with impaired glycemic control.This study investigated the effect of BL6, a MetAP2 inhibitor, on adipogenesis and glucose disposal.To test effect on angiogenesis, Human Umbilical Vein Endothelial Cells(HUVECs) were treated with BL6 for 24h to determine tube formation. Further, to test effect on adipogenesis and glucose disposal, 3T3-L1 pre-adipocytes were treated with BL6(0 µM, 20µM, 50 µM or 100µM) during differentiation. Differentiated cells were stained with Oil Red O for determining lipid accumulation, and glucose uptake assay. Protein levels and RNA expression for key genes involved in the adipogenic cascade were determined.BL6 treatment of HUVECs dose dependently blocked angiogenesis. During differentiation of pre-adipocytes, 50μM and 100µM BL6 significantly reduced lipid accumulation. Treatment with 100µM BL6 significantly decreased expression of adipogenic genes. Interestingly, BL6 treatment dose dependently increased glucose uptake by 3T3-L1 cells.MetAP2 inhibitor blocks angiogenesis, attenuates adipogenesis, yet increases cellular glucose uptake. Collectively this proof of concept study supports a possible role for MetAP2 inhibitor BL6, as a putative anti-obesity therapeutic agent.